DNA methylation profiles of 22 apoptosis-related genes in odontogenic keratocysts before and after marsupialization - Pereira, Karuza Maria Alves (2018)
Objective. Odontogenic keratocysts (OKCs) are cystic lesions of the jaw and tend to recur after treatment. Marsupialization is an effective preliminary treatment for large OKCs. This procedure induces epithelial lining changes in association with reduc- tion of Bcl-2 protein expression, but the underlying mechanisms remain unknown. The purpose of our study was to compare the methylation profile of the apoptosis-related genes of OKCs before and after marsupialization. Study Design. We assessed the methylation percentages of the promoter region of 22 apoptosis-related genes in 13 OKCs, both marsupialized and nonmarsupialized lesions, by using methylation quantitative polymerase chain reaction array. We validated the expression of genes that showed the greatest differences in methylation percentages between the 2 groups. Results. LTBR and BCLAF1 showed higher DNA methylation percentages in the marsupialized OKCs, but this difference did not affect gene expression ( P > .05). The other 20 genes showed similar DNA methylation in both OKC groups. Conclusions. OKCs show a distinct methylation profile after marsupialization, but this is not followed by gene expression alterations. (Oral Surg Oral Med Oral Pathol Oral Radiol 2017;124:483–489)